Structural and magnetic properties of lanthanide compounds: influence of crystallite size and magnetic environment - Palacio, Johny Andres Jaramillo (2023)
The synthesis, crystallographic structure as well the magnetic properties, of the families of double perovskites LaMF e2O6 (M = Bi, Y b), LA2BB′O6 (B = F e, Al- B′ = N i, Co) and the material La0.67Sr0.33MnO3 were studied. The investigated samples were synthesized by the modified Pechini method, the crystalline structure and the lattice parameters were refined by applying the Rietveld method. The greatest constancy with increasing synthesis temperature in the lattice parameters and magnetic properties was found in the La0.67Sr0.33MnO3 material. A superparamagnetic response in the La0.67Sr0.33MnO3, LaBiF e2O6, LaY bF e2O6 and La2AlCoO6 materials, was determined at a synthesis temperature of 873K, which with the increase in the synthesis temperature at different scales for each material became a ferromagnetic response. The material LaY bF e2O6 belonging to the space group (62) P nma with orthorhombic structure, Until now, there are no published articles about this material. The family of perovskites La2BB′O6 (B = F e, Al- B′ = N i, Co) having a double occupancy of La2 presents very similar X-ray diffraction patterns to each other, the materials La2AlCoO6 and La2F eN iO6 crystallize in the space group R − 3C (167) and the La2CoF eO6 material crystallize in the space group P21/n (14), materials that present at low synthesis temperatures magnetic responses of paramagnetism, superparamagnetism and ferromagnetism, respectively.